(untitled) (Indian Journal of Animal Production and Management, 2026)
The study was conducted to determine the effect that oral feeding would have on the Russian hemp seed powder on the ewes assessed based on their measured hormonal, biochemical and protein related parameters. The animals were randomly assigned and placed as three levels of experiment where one of them was a control group )Without any additions( and two levels of experimentation (where the animals were supposed to take the Russian hemp seed powder (200 or 300 mg/ ewe /day) in capsules). In the end of the experiment, blood samples were collected and serum of the samples was assessed on estradiol, follicle-stimulating hormone (FSH), anti-Mullerian hormone (AMH), cholesterol, glucose, urea and creatinine and total protein and globulin. The processing of data was conducted in a completely randomized study on XLSTAT 2016 and multiple range test (Duncan), to determine significant differences in means in P = 0.05. Results have indicated that oral administration of the Russian powder of the hemp seed at different concentration rates had an enormous effect of amplifying the serum estradiol and AMH specific concentration, that is, 300mg/ewe/ day, but not the FSH concentration. On the other hand, serum cholesterol, glucose, urea levels were highly reduced in the treated groups than in the control group yet creatinine was not. Treatment did not significantly differ with a significant change in total protein and globulin. The correlation analysis conducted on Pearson showed that estradiol is significantly correlated with AMH and total protein and globulin between themselves. The received findings allow concluding that oral nutritional supplement of Russian hemp seed powder in a particular dose 300 mg/ewe/day can potentially positively alter certain changes in reproductive hormones and have a positive impact on certain biochemical parameters of ewes.